2013
DOI: 10.1063/1.4788676
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport and shot noise in Thue-Morse sequence graphene superlattice

Abstract: The transport properties and shot noise in Thue-Morse (TM) sequence graphene superlattice are investigated using transfer matrix methods. The results indicate perfect transport with T = 1 is always obtained at normal incidence when incident electrons tunnel through different barrier widths and heights. The zero-k¯-gap and other Bragg gap exhibit different behavior as the barrier width or incident angle increases. Furthermore, the changing of the structure parameters and generation of the TM sequence has a grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…7 In this sense, since the discovery of graphene 8-10 researchers have begun to deal with aperiodic structures based on this prominent material. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] For instance, the Fibonacci sequence is studied in monolayer 11 and bilayer 12 graphene superlattices. In particular, a striking selfsimilar behaviour is reported for different generations number of the aperiodic sequence, 11 it is also found that the transmission spectra are fragmented, and even more appear in groups and the low-energy conductance is considerably amending.…”
Section: Introductionmentioning
confidence: 99%
“…7 In this sense, since the discovery of graphene 8-10 researchers have begun to deal with aperiodic structures based on this prominent material. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] For instance, the Fibonacci sequence is studied in monolayer 11 and bilayer 12 graphene superlattices. In particular, a striking selfsimilar behaviour is reported for different generations number of the aperiodic sequence, 11 it is also found that the transmission spectra are fragmented, and even more appear in groups and the low-energy conductance is considerably amending.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies focus primarily on monolayer graphene, and the preferred mechanism to create the quasi-periodic pattern has been the electrostatic field effect. So far, the quasi-periodic patterns studied in graphene have been Cantor [33][34][35], Fibonacci [36][37][38][39][40], Thue-Morse [41][42][43][44][45][46][47], Double-Period [48] and Gaussian [49,50]. One of the most remarkable characteristics of quasi-periodic patterns in graphene, regardless of the quasi-periodic sequence used, is a zero-gap associated to an unusual Dirac point.…”
Section: Introductionmentioning
confidence: 99%
“…So, by considering the importance of the quasi-periodic modulation, from both the fundamental and technological standpoints, it seems natural that it be an extension for any novel material. To this respect graphene is not the exception, and in the last years the interest in aperiodic or quasi-periodic modulation in graphene is rising [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. All these studies focus primarily on monolayer graphene, and the preferred mechanism to create the quasi-periodic pattern has been the electrostatic field effect.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the plenty of quasi-crystal sequences (QPS) begin to spring up. And the most typical models are Thue-Morse sequence [6]- [8] and CLS [9], [10] sequence. Due to their peculiar optical properties, like self-similarity [11], [12] The associate editor coordinating the review of this manuscript and approving it for publication was Sukhdev Roy.…”
Section: Introductionmentioning
confidence: 99%